Dualism Criminalization Of Homosexual Action - Mohammad Rifky Yunus; Dian Ekawaty Ismail (Estudiante Law Journal, 2022)
This study discusses the Criminalization of Homosexual acts. This research uses normative legal research. It is legal research that places law as a building system' of norma. The system' of Norm build include principals, norms, rules of law, court decision, agreements, doctrins (teachings). The author finda the conclution on this study that the legal vacuum regarding the regulation of same-sex sexual relations is something that we must pay attention to because the absence of law Governing this matter is a matter that is very urgent for the government to review and must make arrangements as soon as possible. Detailed and clear so that it is precise and easy to implement by law enforcement officials.